PENGENALAN UNIT PENANGGULANGAN KEADAAN DARURAT DI BANDARA BAGI SISWA SMK PENERBANGAN DI WILAYAH LAMPUNG DAN SIDOARJO - Nawang Kalbuana; Oke Hendra; Pangsa Rizkina Aswia; Dwi Lestary; Kardi Kardi; Solihin Solihin (Jubaedah : Jurnal Pengabdian dan Edukasi Sekolah (Indonesian Journal of Community Services and School Education), 2021)
PKP-PK unit is an emergency response unit at the airport whose location is within the air-side area that not everyone can enter. The community around the airport and many vocational aviation students have not received comprehensive information related to this PKP-PK Unit. This Unit has a vital role, especially at the time of the accident at the airport. Community Service Activities (PKM) is one of the activities of Tridharma Higher Education that the academic community must carry out at the Polytechnic of Aviation Indonesia Curug. Because it is still in the pandemic condition, Covid-19 PKM activity is done through Webinar with Zoom.  This webinar activity was attended by Vocational Aviation Students in Lampung and Sidoarjo regions in collaboration with Karang Taruna Sedati Gede Sidoarjo village, East Java. After this activity is completed, it is expected that it will increase the knowledge and insight of the students of SmK Flight regarding emergency management units at the airport.